Risk in synthetic biology: views from the lab - McLeod, Carmen; Saille, Stevienna de; Nerlich, Brigitte (EMBO Press/Wiley, 2018)
How do synthetic biologists think about the risks in their research? This paper reports on a novel elicitation method that got surprising answers. Participants reflected not only on technical, but also on societal and psychological risks and responsibilities. Responsible Research and Innovation (RRI), a governance framework supported by many policy makers in the EU and UK, aims to help ensure that societal, as well as technical risks, are addressed at an early stage. However, defining what those risks are is a complex process. We found that when synthetic biologists were allowed to define 'risk' according to their own concerns, they more often chose to explore social and systemic risks to themselves, to science, and to the purposes and motivations of their own research. We argue that RRI as a science governance framework, and synthetic biology as a science, both need to take the wider concerns of scientists in the field as seriously as other potential impacts of emerging technology.